2020
DOI: 10.1107/s2056989020012554
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of monohydrate and methanol solvate compounds of {1-[(3,5-bis{[(4,6-dimethylpyridin-2-yl)amino]methyl}-2,4,6-triethylbenzyl)amino]cyclopentyl}methanol

Abstract: In the title monohydrate compound, 1a, and the methanol solvate compound, 1b, the triethylbenzene derivative, C35H51N5O, has three functionalized side arms and three ethyl groups, the former being located on one side of the central benzene ring, while the latter are directed to the opposite side. Both the crystals are constructed of structurally similar dimers of 1:1 host–guest complexes held together by N—H...O and O—H...N hydrogen bonds, and in 1a additionally by O—H...O hydrogen bonds. The structure of 1b c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Our studies on the molecular recognition of carbohydrates have shown that the participation of different types of recognition groups in the complexation of the substrate favourably influences the binding process (Stapf et al, 2020a,b;Kaiser et al, 2019). Such a combination of two types of recognition units, namely heterocyclic and hydroxy groups, is realised in the triethylbenzene-based title compound 1 (see also Stapf et al, 2020a). The design of the receptors consisting of the aforementioned recognition units was inspired by the nature of the protein binding sites involved in the interactions stabilizing the crystalline protein-carbohydrate complexes (Quiocho, 1989).…”
Section: Chemical Contextmentioning
confidence: 97%
“…Our studies on the molecular recognition of carbohydrates have shown that the participation of different types of recognition groups in the complexation of the substrate favourably influences the binding process (Stapf et al, 2020a,b;Kaiser et al, 2019). Such a combination of two types of recognition units, namely heterocyclic and hydroxy groups, is realised in the triethylbenzene-based title compound 1 (see also Stapf et al, 2020a). The design of the receptors consisting of the aforementioned recognition units was inspired by the nature of the protein binding sites involved in the interactions stabilizing the crystalline protein-carbohydrate complexes (Quiocho, 1989).…”
Section: Chemical Contextmentioning
confidence: 97%
“…Similarly, chip calorimetry experiments were performed with one of our receptor compounds possessing [1-(hydroxymethyl)cyclopent-1-yl]amino moieties (Lerchner et al, 2022). Further compounds bearing hydroxy groups, whose crystal structures we have recently discussed (Stapf et al, 2020b(Stapf et al, , 2022, are currently being investigated for their ability to act as receptors for carbohydrates. In this article, we describe the crystal structures of the formamide monosolvate and the n-propanol/ H 2 O solvate/hydrate of compound 1 containing the 2,6-bis-(hydroxymethyl)-4-methylphenoxy moiety, which represents a new structural unit for the design of carbohydrate receptors.…”
Section: Chemical Contextmentioning
confidence: 99%
“…This aggregate is stabilized by a total of eight hydrogen bonds. The crystal structures of the monohydrate and the methanol solvate of {1- [(3,5-bis[(4,6-dimethylpyridin-2-yl)aminomethyl]-2,4,6-triethylbenzyl)amino]cyclopentyl}methanol (CAD-TAG, CADTEK; Stapf et al, 2020b) are composed of structurally similar dimers of 1:1 host-guest complexes. In the crystal structure of the diethyl ether solvate of 1-(bromomethyl)-3,5-bis [(4,6-dimethylpyridin-2-yl)aminomethyl]-2,4,6triethylbenzene (BIYTOT; Mazik & Kuschel, 2008b), the host molecule adopts a conformation with a complete up-down alternation of the side chains on the benzene ring (for discussions on conformations of 1,3,5-trisubstituted 2,4,6-trialkylbenzene-based compounds, see: Koch et al, 2017;Schulze et al, 2017).…”
Section: Database Surveymentioning
confidence: 99%
“…Compounds consisting of a 1,3,5-trisubstituted 2,4,6-trialkylbenzene scaffold have been recognized to possess the ability to act as artificial receptors for various neutral and ionic substrates, such as carbohydrates (Mazik, 2009(Mazik, , 2012, ion pairs (for example, hydronium/hydroxide ions; Stapf et al, 2015) and ammonium ions (Chin et al, 2002;Jonah et al, 2017;Schulze et al, 2018). In the case of carbohydrate-binding agents (artificial carbohydrate receptors), both acyclic (Kaiser et al 2019;Stapf et al, 2020aStapf et al, , 2020bKö hler et al, 2020) and macrocyclic compounds (Lippe & Mazik, 2013, 2015Amrhein et al, 2016;Amrhein & Mazik, 2021) have been developed. Bromomethyl-and/or phthalimidomethyl-functionalized trialkylbenzenes are often used as precursors for the syntheses of such compounds .…”
Section: Chemical Contextmentioning
confidence: 99%